2020
DOI: 10.1007/s42452-020-03537-w
|View full text |Cite
|
Sign up to set email alerts
|

Potassium hydrogen sulfate mediated kinetics and mechanism of oxidation of certain polyols by Quinolinium bound Cr(VI) reagents

Abstract: Potassium hydrogen sulfate (KHSO 4) mediated oxidation of certain alcohols (Polyols) has been studied by quinolinium bound Cr(VI) reagents like quinolinium dichromate (QDC) and quinolinium chlorochromate (QCC) at different temperatures. Reaction kinetics revealed second order kinetics with a first order in [Alcohol] and [Cr(VI) reagent] at constant bisulfate concentration. Ten fold variation of added [KHSO 4 ] enhanced the observed rateconstant (k′) by ten fold, showing first order dependence on [KHSO 4 ]. Mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…The reaction was examined across various NaClO4 concentrations, from 1.33 x 10 -2 to 4.66 x 10 -2 M. Interestingly, the reaction rates remain constant, indicating the involvement of primary and secondary salt effects, potentially nullifying each other. A literature study also supports the observed findings (23)(24)(25).…”
Section: Effect Of Adding Saltsupporting
confidence: 86%
See 1 more Smart Citation
“…The reaction was examined across various NaClO4 concentrations, from 1.33 x 10 -2 to 4.66 x 10 -2 M. Interestingly, the reaction rates remain constant, indicating the involvement of primary and secondary salt effects, potentially nullifying each other. A literature study also supports the observed findings (23)(24)(25).…”
Section: Effect Of Adding Saltsupporting
confidence: 86%
“…The observed negative value of entropy of activation (ΔS ‡ ) indicates that the intermediate complex is more polar compared to the initial reactants. The overall decrease in entropy during complex formation is typically due to the loss of translational energy required to bring multiple reactants together at the transition state (23,30,31).…”
Section: Rtmentioning
confidence: 99%